Effects of surface roughness on wettability and surface energy of coal - Zhang, Jian; Xu, Bo; Zhang, Pengyan; Cai, Maolin; Li, Bo (Frontiers in Earth Science, 2023)
Surface roughness has an important effect on the wettability and surface energy of coal. Although the predecessors had studied the effect of surface roughness on the wettability of coal, there were few researches on the effect of surface energy of coal, and the relationship between wettability and surface energy had not been thoroughly studied. This paper aimed to study the effect of surface roughness on the wettability and surface energy of coal, and revealed the relationship between the wettability and surface energy of coal. Based on the surface roughness of coal, this paper selected Hami lignite, Anyang coking coal and Zhaogu anthracite as the research objects, used the experimental methods to measure the surface roughness and experimental contact angle of coal under different conditions to study the effect of surface roughness on the wettability, and then applied the OWRK method to calculate the surface energy of coal to study the effect of surface roughness on the surface energy. The experimental results showed that the wettability of hydrophilic coal became better and the surface energy increased with the increase of surface roughness, while the results of hydrophobic coal were opposite. There was a positive correlation between the wettability and surface energy of coal, and the wettability of coal could be analyzed from the perspective of surface energy. Surfactant could change the wettability of coal, but unchanged the law of wettability with surface roughness.